Managing Grazing to Restore Soil Health, Ecosystem Function, and Ecosystem Services - Teague, Richard; Kreuter, Urs (Frontiers in Sustainable Food Systems, 2020)
Ruminants including domestic livestock, have been accused of causing damaging impacts on the global environment and human well-being. However, with appropriate management, ruminant livestock can play a significant role in efforts to reverse environmental damages caused by human mismanagement and neglect. Worldwide, at least one billion people living in grazing ecosystems depend on them for their livelihoods, usually through livestock production, and for other ecosystem services that affect human well-being. For long-term rangeland sustainability and ecological resilience, agricultural production policies are urgently needed globally to transform current damaging industrial inorganic input agricultural practices to resource conservation practices that enhance ecosystem function. This is supported by evidence that farmers and ranchers who apply regenerative management practices to restore ecosystem functionality create sustainable, resilient agroecosystems cost-effectively. With enhanced management of grazing resources, domesticated ruminants can be used to produce higher permanent soil cover of litter and plants, which are effective in reducing soil erosion and increasing net biophysical carbon accumulation. Incorporating forages and ruminants into regeneratively managed cropping systems can also elevate soil organic carbon and improve soil ecological function and reduce production costs by eliminating the use of annual tillage, inorganic fertilizers and biocides. Ecosystem services that are enhanced using regenerative land management include soil stabilization and formation, water infiltration, carbon sequestration, nutrient cycling and availability, biodiversity, and wildlife habitat, which cumulatively result in increased ecosystem and economic stability and resilience. Scientists partnering with farmers and ranchers around the world who have improved their land resource base and excel financially have documented how such land managers produce sound environmental, social, and economic outcomes. Many of these producers have used Adaptive Multi-Paddock (AMP) grazing management as a highly effective approach for managing their grazing lands sustainably. This approach uses short-duration grazing periods, long adaptively varied post-grazing plant recovery periods requiring multiple paddocks per herd to ensure adequate residual biomass, and adjustment of animal numbers as environmental and economic conditions change. Using this approach, farmers and ranchers have achieved superior ecosystem and profitability outcomes. This manuscript summarizes the use of AMP grazing as regenerative tool for grazed and rotationally cropped lands.